Analisis Kondisi Sosial Ekonomi Petani Terhadap Kerusakan Lahan di DAS Biyonga Kabupaten Gorontalo - Abdulah, Sri Wulan; Jaya, Risman; Dangkua, Talha (UNIVERSITAS NEGERI MAKASSAR, 2020)
This research was conducted at Biyonga Sub-watershed area of Gorontalo Regency. The aim of this research was to determine the effect of the socio-economic status of farmers on land damageand determine the behavior of farmers in land management in the Biyonga Sub-Watershed area, Gorontalo Regency. The researcher used descriptive quantitative method with Chi-Square test as data analysis technique. The results of the research showed that socio-economic factors that affecting land damage in the Biyonga Sub-Watershed are the educational status of farmers. They are predominantly elementary school graduates with lower income. This factor encouraged them to depend more on agricultural land. Farmers have suffiecient knowledge of good agricultural land management, but they do not care about the benefits and objectives of land conservation.